Improvement in impact resistance performance of glass/epoxy composite through carbon nanotubes and silica nanoparticles. (September 2018) - Naghizadeh, Zahra; Faezipour, Mehdi; Pol, Mohammad Hossein; Liaghat, Gholam Hossein; Abdolkhani, Ali
Experimental studies are presented on the high velocity impact behavior of nanomaterial dispersed resin viz laminates made using E-glass fabric with epoxy resin. The nanomaterials used are silica nanoparticles and carboxyl functionalized multi-walled carbon nanotube (COOH-MWCNT) for polymer matrix composites. The composites' ballistic limit ( Vbl ) and impact energy absorbed ( Eab ) were determined by subjecting the material to impact loading of 85, 100, and 112 m/s by conical nose projectile. It was found that the high velocity impact response of epoxy composites improved when a nanomaterial was used as reinforcement. COOH-MWCNTs reinforced composites exhibited better energy absorption than silica nanoparticles composites. Moreover, the damage pattern for different types of materials studied is presented. It is observed that the damage size on the target around the point of impact decreases on addition of nanoparticles especially COOH-MWCNTs. Quantitative data are presented for high velocity impact behavior of the seven types of specimens studied.